Big Book of Juices - Savona,Natalie (London, UK Duncan Baird / Watkins Publ (UK), 2016)
With some 405 recipes for fruit and vegetable juices, smoothies, and quenchers, this updated and expanded edition of Natalie Savona's best-selling guide to juicing now offers health-conscious readers even more. A clever indexing system sorts the juices by key ingredients, by nutrients, and by health benefits